2022
DOI: 10.1186/s13256-022-03545-x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired pure red cell aplasia after severe acute respiratory syndrome corona virus 2 infection: a case report

Abstract: Background Coronavirus disease 2019, caused by severe acute respiratory coronavirus 2, has been responsible, since December 2019, for a severe pandemic resulting in millions of deaths worldwide, and the number is still increasing. Although coronavirus disease 2019 is mostly a respiratory syndrome, it is considered a multisystemic disease and shows clinical diversity with a wide range of manifestations including hematological features. Case presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In our case, AIHA and PRCA were induced after a low-grade symptom of COVID-19 associated with mild fever, suggesting that slight or asymptomatic COVID-19 infection could cause such hematological disturbances. Although previous reports on COVID-19-associated PRCA that were resistant to PSL treatment and recovery after the administration of cyclosporine [ 15 ] or tacrolimus [ 13 ] were published, our case and the case by Karrat et al [ 12 ] showed a good response to PSL as shown in Table 2 . The case by Ghimire et al [ 14 ] also showed a response to dexamethasone.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In our case, AIHA and PRCA were induced after a low-grade symptom of COVID-19 associated with mild fever, suggesting that slight or asymptomatic COVID-19 infection could cause such hematological disturbances. Although previous reports on COVID-19-associated PRCA that were resistant to PSL treatment and recovery after the administration of cyclosporine [ 15 ] or tacrolimus [ 13 ] were published, our case and the case by Karrat et al [ 12 ] showed a good response to PSL as shown in Table 2 . The case by Ghimire et al [ 14 ] also showed a response to dexamethasone.…”
Section: Discussionmentioning
confidence: 55%
“…Our case was associated with simultaneous occurrence of AIHA and PRCA after COVID-19. As per our search, simultaneous occurrence of AIHA and PRCA [ 14 , 15 ], or occurrence of PRCA [ 12 , 13 ] after COVID-19 have rarely been reported. Those reported patients including our case are summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation